Poems by Emily Dickinson, Series One - Dickinson, Emily, 1830-1886; Higginson, Thomas Wentworth, 1823-1911; Todd, Mabel Loomis, 1856-1932 (Salt Lake City, UT : Project Gutenberg, 2001)
"Poems by Emily Dickinson, Series One" by Emily Dickinson is a collection of poetry written in the late 19th century, during the Victorian era. This notable compilation showcases Dickinson's introspective and often unconventional voice, examining themes such as love, nature, death, and the complexities of the human experience. Her work is characterized by innovative use of punctuation, particularly dashes, and a unique structure that defies conventional poetic forms. The collection contains a wide array of themes and emotions, ranging from the profound to the whimsical. In her poems, Dickinson explores the nature of success, love, and existence, often questioning societal norms and the expectations placed upon individuals. She weaves intricate imagery and profound insight into her verses, drawing connections between the natural world and human feelings. The poet's voice is intimate and contemplative, reflecting her solitary life and deep observations of the world around her. Ultimately, the collection invites readers to reflect on their own experiences and the universal truths that bind humanity together. (This is an automatically generated summary.)
Release date is 2001-06-01
Etext scanned by Jim Tinsley
Keywords: American poetry